Rapid Purification and Properties of Betaine Aldehyde Dehydrogenase from Pseudomonas aeruginosa - Velasco-García, Roberto (American Society for Microbiology, 1999)
Betaine aldehyde dehydrogenase (BADH) (EC 1.2.1.8) catalyzes the last, irreversible step in the synthesis of the osmoprotectant glycine betaine from choline. In Pseudomonas aeruginosa this reaction is also an obligatory step in the assimilation of carbon and nitrogen when bacteria are growing in choline or choline precursors. We present here a method for the rapid purification to homogeneity of this enzyme by the use of ion-exchange and affinity chromatographies on 2′,5′-ADP–Sepharose, which results in a high yield of pure enzyme with a specific activity at 30°C and pH 7.4 of 74.5 U/mg of protein. Analytical ultracentrifugation, gel filtration, chemical cross-linking, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis suggest that BADH from P. aeruginosa is a homodimer with 61-kDa subunits. The amino acid composition and the N-terminal sequence of 21 amino acid residues showed significant similarity with those of the enzymes from Xanthomonas translucens and Escherichia coli. Neither BADH activity nor BADH protein was found in cell extracts from bacteria grown in the absence of choline. In contrast to other BADHs studied to date, the Pseudomonas enzyme cannot use positively charged aldehydes other than betaine aldehyde as substrates. The oxidation reaction has an activation energy of 39.8 kJ mol(−1). The pH dependence of the velocity indicated an optimum at pH 8.0 to 8.5 and the existence of two ionizable groups with macroscopic pK values of 7.0 ± 0.1 and 9.7 ± 0.1 involved in catalysis and/or binding of substrates. The enzyme is inactivated at 40°C, but activity is regained when the heated enzyme is cooled to 30°C or lower. At the optimum pH of 8.0, the enzyme is inactivated by dilution, but it is stable at pH 6.5 even at very low concentrations. Also, P. aeruginosa BADH activity is rapidly lost on removal of K(+). In all cases studied, inactivation involves a biphasic process, which was dependent on the enzyme concentration only in the case of inactivation by dilution. NADP(+) considerably protected the enzyme against these inactivating conditions.